Intraspecific Crossability in Andrographis paniculata Nees: A Barrier against Breeding of the Species - Alireza Valdiani; Mihdzar Abdul Kadir; Mohd Said Saad; Daryush Talei; Vahid Omidvar; Chia Sok Hua (The Scientific World Journal)
The ambiguity of crossability in Andrographis paniculata (AP) was pointed out in the present research. Accordingly, the effects of different style length and crossing time on intraspecific crossability of seven AP accessions in 21 possible combinations were investigated. The best results came out between 08:00 to 11:00 h for manual out-crossing of AP, while the time from 12:00 to 18:00 h showed a decreasing trend. Moreover, 12 mm style length was found as the most proper phenological stage in terms of stigmatic receptivity to perform out-crossing in this plant. All in all, AP behaved unlikely in each combination, and a significant difference was observed in crossability of AP accessions (𝑃<0.01). The lowest and highest crossability rate was found in hybrids 21 (11261NS × 11344K) and 27 (11322PA × 11350T) with 0.25% and 13.33%, respectively. Furthermore, a significant negative relationship between style length and crossibility (𝑟2=0.762∗∗) was recorded in this research. As a final conclusion, crossing time and proper style length can improve the intraspecific crossability in the species, considerably. Despite all the mentioned contrivances, we still believe that a genetic incongruity should be involved as an additional obstacle in crossability of those combinations that failed or responded deficiently to outcrossing.